A sparse approach to mixed weak type inequalities. - Caldarelli, Marcela; Rivera Ríos, Israel P. (Springer Nature, 2019)
Abstract. In this paper we provide some quantitative mixed weak-type estimates assuming conditions that imply that uv ∈ A∞ for Calder´on-Zygmund operators, rough singular integrals and commutators. The main novelty of this paper lies in the fact that we rely upon sparse domination results, pushing an approach to endpoint estimates that was introduce din Domingo-Salazar et al. (Bull Lond Math Soc 48(1):63–73, 2016) and extended in Lerner et al. (Adv Math 319:153–181, 2017) and Li et al. (J Geom Anal, 2018).
https://openpolicyfinder.jisc.ac.uk/id/publication/8107
Keywords: Análisis matemático; Desigualdades (Matemáticas); Mixed weak type inequalities; Sparse